Study of piezoelectric properties for electromechanical applications in PVDF composites reinforced with barium titanate nanorods - Jiaad, Suaad M.; Jasim, Safaa A. (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to examine how the use of Barium titanate (BaTiO₃) nanorods enhances the electromechanical and mechanical properties of a Polyvinylidene Fluoride (PVDF) matrix. Polyvinylidene Fluoride composites with various amounts of barium titanate (0, 3, 6, 9, 12 and 15 wt%) were prepared and tested for their mechanical behaviour using a tensile test. The results show that increasing the levels of Barium titanate up to 9 wt.% increased elastic modulus and tensile strength while they decreased afterwards. Conversely, an increase in elongation at break showed that higher concentrations contain more stiffness than less ones. As for the electrical and mechanical conductance attributes of barium titanate, the tests showed that when the concentration increased, its sensitivity increased as well with an optimal amount of barium titanate being 15 wt%. In this case, the proper proportion of barium titanate for those composites is 9.0wt% so as to optimize piezoelectric property at the same time maintain mechanical strength. The improvement ratio in output voltage for the PVDF nanocomposites was found to be 1.45 times (45%) that of the polymer without barium titanate nanorods, indicating an enhancement in the material's piezoelectric responsiveness. This information can be used by designers in high strength advanced composites in order to improve their piezoelectric properties for improved performance in electromechanical applications.